Supercritically-Dried Porous Silicon Powders with Surface Areas Exceeding 1000 m2/g. (1st January 2015) - Loni, A.; Canham, L. T.; Defforge, T.; Gautier, G.
Abstract : Porous silicon micro-particulates have been harvested after electrochemical anodization of lightly-doped p-type silicon wafers in hydrofluoric acid electrolyte containing sulfuric acid as an additive. Post-anodization, significantly higher internal surface areas per unit mass have been realized by utilizing super-critical drying with CO2 solvent instead of air-drying, with up to 1125 m 2 /g being achieved. Correspondingly higher pore volumes are also evident (>1 cm 3 /g) and, with average pore diameters ranging between 3–4 nm, a higher micropore content is made accessible. It is proposed that the improvements achieved through super-critical drying indicate that the higher density of micropores expected from the choice of wafer resistivity and electrolyte composition (their presence being confirmed through analysis of the adsorption-desorption isotherms) is facilitated through a higher degree of integrity being maintained within the etched pore structure during electrolyte removal.